Centro orgánico de acopio, procesamiento y transporte productos agrícolas en zonas costeras del Bajo Baudó. (2022)
In the world, coastal areas represent a great importance in commercial activities, residential, tourist activities between backwards, that elaborates the human being. These are areas that attract considerable population becoming points of development have resources and are of great potential for society, as productive ecosystems either through the use of these ecosystems or the implementation of tourism activities that benefit the economy of the area. This is how the economy develops in most of the world in coastal areas, but in Colombia these areas with so much potential does not have the same benefits or equity to be able to develop properly, whereas these areas with great potential in the world are areas of greater poverty in the world. Likewise, the lack of connectivity of these areas with the rest of the country is one of the most important issues to address. The design of ports to docks that have complementary activities for the benefit of communities and thus generate organic models that can be replicated in areas with the same conditions determining the approach of the architectural discourse of the project, an organic port center that allows not only the connection of these areas but also support for the use of productive agricultural areas.